(untitled) (Indian Journal of Veterinary Pathology, 2025)
The current investigation was conducted to assess the anti-osteoporotic potential of microalgal Spirulina protein fortified with leaf powder of Moringa and Finger millet (MSMF) in female Wistar rat model of Methylprednisolone induced osteoporosis. The study included six groups of six rats each. Group I (normal control) rats, received distilled water orally daily for seven weeks, Group II (disease control) to VI rats received Methylprednisolone @ 40 mg/kg bw subcutaneously thrice a week for six weeks from 2nd to 7th week of the experimental period. Additionally, Group III (reference control) rats received Alendronate at 40 µg/kg body weight subcutaneously three times a week for the same duration. Group IV, V and VI rats received MSMF @ 500, 1000 and 2000 mg/kg bw respectively, daily orally for seven weeks, along with Methylprednisolone. Group II rats showed significant decrease in feed intake, body weight, femur weight, haemato-biochemical parameters, radiological and histopathological parameters of the femur. The changes caused by Methylprednisolone were alleviated in Alendronate group and MSMF treatment groups in a dose dependent manner. Histopathologically, the MSMF treatment groups showed substantial improvement in trabecular thickness, cortex thickness, osteocyte number, reduction in resorption cavities and erosion of cartilage. The anti-osteoporotic efficacy of MSMF @ 500 mg/kg was lower than that of Alendronate, while the MSMF @ 1000 mg/kg and 2000 mg/kg bw showed better efficacy than MSMF @ 500 mg/kg and equivalent to the effects of Alendronate.